Evaluation of some hormones in patients with major β-Thalassemia in the Nineveh Governorate - Iraq - Al-Azzawi, Zeena Zuhair Ibrahim; Jankeer, Muna Hussein (Acta Scientiarum. Animal Sciences, 2024)
Thalassemia is one of the most important genetic haemolytic diseases that cause the breakdown of red blood cells (RBCs) in patients with β-Thalassemia major. The body does not produce enough haemoglobin, which is an important part of RBCs. When there is not enough haemoglobin, RBCs do not function properly in the body, so the condition continues for short periods of time. The current studies aimed to determine the extent of the impact of β-Thalassemia major on some hormonal variables in the serum of 80 patients (40 males and 40 females) aged between (1-15) years, in addition to 20 healthy children of the same age range and of both sexes, who were considered as a control group. The results of this study showed a significant increase in the concentration of erythropoietin (EPO) by 187% in the serum of patients with β-Thalassemia major compared to healthy of both sexes, with an increase of 188 in males and 183% in females. The highest significant increase was in the age group of (11-15) years in males and females compared to healthy control. The results also showed a significant decrease in the concentration of hepcidin and growth hormones in the serum of patients with a decrease of 55 and 56% respectively compared to healthy individuals of both sexes, with a highest significant decrease of 56 and 59% in males, and 55 and 52% in females respectively. The highest significant decrease was in the age group of (11-15) years for both hormones in males and females compared to healthy control based on age groups and sex.